Antibiotic prescribing practices for prophylaxis and therapy of oral/dental infections in pediatric patients - results of a cross-sectional study in Turkey - Sirinoglu Capan, Belen; Duman, Canan; Kalaoglu, Elif Ece (German Medical Science GMS Publishing House, 2023)
Aim: Antibiotics are often prescribed for the treatment of various infections and prophylactic purposes in dental practice. Their improper use can cause microbial resistance to antibiotics, which poses a world-wide threat. The aim of this cross-sectional study was to evaluate the edge and attitudes of dentists and dentistry students about antibiotic prescription practices for prophylaxis and the treatment of dental infections in pediatric patients.Methods: A questionnaire was e-mailed to 2,100 dentists and 300 senior dentistry students. The questionnaire was filled out by the participants within a 2-month period (May-June 2020). A 30-point scoring system was developed to assess the knowledge levels of the dentists according to the guidelines. Descriptive statistical analyses were performed. One-way ANOVA test and the Chi-Squared test were used to compare qualitative variables.Results: The response rate was found to be 24.2% for dentists and for senior dentistry students. 19.4% of the participants were found to be moderately able and 80.6% of them were highly knowledgeable. Students' knowledge scores were found to be higher than the general dentists and other specialists (p<0.05). There was no significant difference between students and pedodontists.Conclusion: Dentists were found to have sufficient knowledge about the usage of antibiotics in children, but there is still a lack of information about circumstances under which antibiotics should not be prescribed. Dentists and dentistry students should attend continuing education programs to keep their information up-to-date and should also prescribe antibiotics in adherence with the current guidelines to prevent antibiotic resistance.